PENGARUH KOORDINASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI SEKRETARIAT KOTA ADMINISTRASI JAKARTA SELATAN - Ahmad Syauqi (Prima Center Indonesia, 2019)
Modern organizational management has become a major need to improve the quality of public services which is the task of regional devices. The city of South Jakarta Administration as an element of the Governor's assistance, requires apparatus resources in carrying out tasks and for the realization of productive, effective and efficient regional device performance. In carrying out the Tasks and Functions of the South Jakarta Administrative City, currently there are several obstacles such as the absence of Minimum Service Standards as a basis for determining performance-based budgets and the amount of budget needed to provide a public service, temporary measurement tools only provided from the Provincial Level.Keywords: coordination, discipline, performance